Inclusive education: teachers' professional self-concept (Research, Society and Development, 2021)
The inclusive education teacher's professional self-concept is the perception he has of himself in relation to teaching and the tasks he performs in this educational context. This study aimed to analyze the professional self-concept of teachers in the context of inclusive education. As a method, descriptive and inferential statistics were used to analyze the data collected with two instruments, the first sought information about a) knowledge about the legislation and norms that govern inclusive education; b) teacher confidence in teaching for students with disabilities; and c) teachers' experience in teaching students with disabilities. The second instrument was the Professional Self-Concept Scale of Teachers (EAPP), consisting of 36 items, distributed over four dimensions: Care in the interpersonal relationship in the school context; Safety in the school work context; Bond (belonging) and cooperation in the school context and Professional recognition in the school context. The sample was for convenience, consisting of 41 teachers who work in inclusive education in a city in Bahia. The results of this research reveal that teachers with more experience in teaching students with disabilities feel more competent; those who know the regulations on inclusive education collaborate more with the group and those who have a high level of confidence in teaching with students with disabilities are more confident in the profession. The study concludes that the teacher's general self-concept in the context of inclusive education is positive, being higher in the factors Care in the interpersonal relationship; and Bond/belonging in the school context of inclusive education; and slightly lowered in the factors Safety in the school work context; and job recognition.